Assessment of the quality of life of patients after neurosurgical treatment for cerebral vascular pathology - — — (Ukrainian Neurosurgical Journal, 2007)
Abstracts of the Conference of neurosurgeons of Ukraine "Life quality criteria at patients after neurosurgical operations", September 27–28, Koktebel, AR Crimea, Ukraine